Role of Paralegal in Providing Access to Justice for the Poor: Comparing Indonesia and Malaysia - Muhammad Bagas Ragil Wicaksono; Hakim Anis Malik (Universitas Negeri Semarang, 2022)
The Law on Legal Aid describes the duties and authorities of Paralegals, in practice several times it became controversial when previously paralegals were allowed to participate in proceedings in court, but after the Supreme Court's decision Number 22 P/HUM/2018 there were several articles that were deleted. Then, the role of paralegals can be maximized in providing legal assistance, especially for the underprivileged. The provision of legal aid can also be implemented properly if all stakeholders can synergize properly, one of which is with law enforcement as the cornerstone of the reflection of law in Indonesia. In several case studies, there have been many roles of paralegals who can provide non-litigation legal assistance to the general public, especially the poor and marginalized. In this case, there is concern about the role of law students which can also be maximized as a guard in legal counseling to the community, as well as sustainable assistance. It is hoped that the more people who are aware of the law will grow, the public's confidence in the law in Indonesia will also increase.